Energy and protein requirements for maintenance and growth of Boer crossbred kids - Fernandes, M. H. M. R.; Resende, Kleber Tomás de [UNESP]; Tedeschi, L. O.; Fernandes, J. S.; Silva, H. M.; Carstens, G. E.; Berchielli, T. T.; Teixeira, I. A. M. A.; Akinaga, L. (Amer Soc Animal Science, 2007)
Meat production by goats has become an important livestock enterprise in several parts of the world. Nonetheless, energy and protein requirements of meat goats have not been defined thoroughly. The objective of this study was to determine the energy and protein requirements for maintenance and growth of 34 3/4 Boer x 1/4 Saanen crossbred, intact male kids (20.5 +/- 0.24 kg of initial BW). The baseline group was 7 randomly selected kids, averaging 21.2 +/- 0.36 kg of BW. An intermediate group consisted of 6 randomly selected kids, fed for ad libitum intake, that were slaughtered when they reached an average BW of 28.2 +/- 0.39 kg. The remaining kids (n = 21) were allocated randomly on d 0 to 3 levels of DMI (treatments were ad libitum or restricted to 70 or 40% of the ad libitum intake) within 7 slaughter groups. A slaughter group contained 1 kid from each treatment, and kids were slaughtered when the ad libitum treatment kid reached 35 kg of BW. Individual body components (head plus feet, hide, internal organs plus blood, and carcass) were weighed, ground, mixed, and subsampled for chemical analyses. Initial body composition was determined using equations developed from the composition of the baseline kids. The calculated daily maintenance requirement for NE was 77.3 +/- 1.05 kcal/kg(0.75) of empty BW (EBW) or 67.4 +/- 1.04 kcal/kg(0.75) of shrunk BW. The daily ME requirement for maintenance (118.1 kcal/g(0.75) of EBW or 103.0 kcal/kg(0.75) of shrunk BW) was calculated by iteration, assuming that the heat produced was equal to the ME intake at maintenance. The partial efficiency of use of ME for NE below maintenance was 0.65. A value of 2.44 +/- 0.4 g of net protein/kg(0.75) of EBW for daily maintenance was determined. Net energy requirements for growth ranged from 2.55 to 3.0 Mcal/kg of EBW gain at 20 and 35 kg of BW, and net protein requirements for growth ranged from 178.8 to 185.2 g/kg of EBW gain. These results suggest that NE and net protein requirements for growing meat goats exceed the requirements previously published for dairy goats. Moreover, results from this study suggest that the N requirement for maintenance for growing goats is greater than the established recommendations.
Keywords: comparative slaughter; goat; net requirement; Nutrition; production